Determination of the critical chain length for macromolecular crystallization using structurally flexible polyketones. Issue 34 (23rd August 2022) - Ide, Yuki; Manabe, Yumehiro; Inaba, Yuya; Kinoshita, Yusuke; Pirillo, Jenny; Hijikata, Yuh; Yoneda, Tomoki; Shivakumar, Kilingaru I.; Tanaka, Saki; Asakawa, Hitoshi; Inokuma, Yasuhide
Abstract : Critical chain length dividing small-molecule crystallization from macromolecular crystallization was determined for discrete polyketones to be as short as pentamer. Abstract : Critical chain length that divides small molecule crystallization from macromolecular crystallization is an important index in macro-organic chemistry to predict chain-length dependent properties of oligomers and polymers. However, extensive research on crystallization behavior of individual oligomers has been inhibited by difficulties in their synthesis and crystallization. Here, we report on the determination of critical chain length of macromolecular crystallization for structurally flexible polyketones consisting of 3, 3-dimethylpentane-2, 4-dione. Discrete polyketone oligomers were synthesized via stepwise elongation up to 20-mer. Powder and single crystal X-ray diffraction showed that the critical chain length for polyketones existed at an unexpectedly short chain length, 5-mer. While shorter oligomers adopted unique conformations and packing structures in the solid state, higher oligomers longer than 4-mer produced helical conformations and similar crystal packing. The critical chain length helped with understanding the inexplicable changes in melting point in the shorter chain length region resulting from chain conformations and packing styles.